Evaluation of Chikungunya diagnostic assays: differences in sensitivity of serology assays in two independent outbreaks. - Grace Yap; Kwoon-Yong Pok; Yee-Ling Lai; Hapuarachchige-Chanditha Hapuarachchi; Angela Chow; Yee-Sin Leo; Li-Kiang Tan; Lee-Ching Ng (Public Library of Science (PLoS), 2010)
BACKGROUND: The sensitivity and specificity of two in-house MAC-ELISA assays were tested and compared with the performance of commercially-available CTK lateral flow rapid test and EUROIMMUN IFA assays for the detection of anti-Chikungunya virus (CHIKV) IgM. Each MAC-ELISA assay used a whole virus-based antigen derived from genetically distinct CHIKV strains involved in two chikungunya disease outbreaks in Singapore (2008); a January outbreak strain with alanine at amino acid residue 226 of the E1 glycoprotein (CHIKV-A226) and a May-to-September outbreak strain that possessed valine at the same residue (CHIKV-226V). We report differences in IgM detection efficacy of different assays between the two outbreaks. The sensitivities of two PCR protocols were also tested. METHODS AND FINDINGS: For sera from January outbreak, the average detection threshold of CTK lateral flow test, MAC-ELISAs and EUROIMMUN IFA assays was 3.75, 4.38 and 4.88 days post fever onset respectively. In contrast, IgM detection using CTK lateral flow test was delayed to more than 7 days after fever onset in the second outbreak sera. However, MAC-ELISA using CHIKV-226V detected IgM in the second outbreak sera 3.96 days after fever onset, which was approximately one day earlier compared to the same assay using CHIKV-A226 (4.86 days). Specificity was 100% for both commercial assays, and 95.6% for the in-house MAC-ELISAs. For sensitivity determination of the PCR protocols, the probe-based real time RT-PCR method was found to be 10 times more sensitive than one based on SYBR Green. CONCLUSION: Our findings suggested that the two strains of CHIKV using variants A226 and 226V resulted in variation in sensitivities of the assays evaluated. We postulated that the observed difference in antigen efficacy could be due to the amino acid substitution differences in viral E1 and E2 envelope proteins, especially the E1-A226V substitution. This evaluation demonstrates the importance of appraisal of different diagnostic assays before their application in clinical and operational settings.